GIVING STIMULUS OF CHILDREN DEVELOPMENT AGES 3 - 5 YEARS OLD - Widiantoro, Eko; prawesti, Dian (Jurnal Penelitian STIKES Kediri, 2013)
Stimulus is an activity to stimulate the basic ability of children so can grow and develop optimally. Lack of giving stimulus at children can cause deviation of social behavior and motor. The objective of the research is to analyze corelation giving stimulus by parents with development of children ages 3-5 years in Early Age Children Education Star Gardu Sehati (Kelurahan Tinalan Kecamatan Pesantren Kota Kediri). The design of the research was correlations. The population of the research was the parent and child 3-5 years age were 54 respondents. Data was analyzed using Chi square with significant level Î± < 0.05. The results obtained by the stimulus giving parents found 24.63% less and child development as well as a distorted dubious 31.48%, so h0 is rejected which means there are correlation giving stimulus by parents with development of children ages 3-5 years age. The conclusion was if the parents giving good growth stimulus accordance with the developmental stages of children have normal development.